Paneuropa oder Eurafrika? Richard Nikolaus Coudenhove-Kalergis koloniale Ambitionen in der Zwischenkriegszeit - Moritz Oberhollenzer (Historia.scribere)
The following paper talks about the colonialist plans of Richard Nikolaus Coudenhove-Kalergi, who is often praised as a pioneer of European unification, in the interwar period. As is shown, Coudenhove‘s colonialist ambitions were inspired by his exaltation of European culture and his dread of its destruction. His racist views upon humankind, in combination with his quasi-nationalist views upon an idealised version of Europe and his fear of the destruction thereof, were what made them compatible with his other ideas.